Headspace sampling‐gas chromatograph‐mass spectrometer as a screening method to thermally extract fireground contaminants from retired firefighting turnout jackets. (24th July 2020) - Shinde, Adhiraj; Ormond, R. Bryan
SUMMARY: Firefighters are at a 1.5 to 2 times greater risk of contracting certain types of cancers as compared to the general population. After preliminary studies, it was evident that contaminated turnout gear and ensemble elements could be linked to heightened cancer rates amongst firefighters. Compounds such as polycyclic aromatic hydrocarbons (PAHs), perfluorinated compounds, phenols, phthalates, brominated flame retardants, dioxins, volatile organic compounds, and many others are present in the contaminated gear, of which many are known carcinogens. A setup of headspace sampler‐gas chromatograph‐mass spectrometer was used to measure the off‐gassing of the fabric samples taken from retired field‐contaminated turnout jackets. The fabric samples were exposed to a specific temperature and allowed to equilibrate for a fixed time in the HS. A custom reference mix of phenols, phthalates and PAHs was put together to develop standard calibration curves. The compounds off‐gassing from the outer shell, thermal liner and the moisture barrier were analyzed and the masses of certain marker compounds were calculated based of the standard calibration curves. The technique could be used as a screening method to thermally extract contaminants from field‐contaminated firefighter turnout materials such as jackets, pants, gloves, and so on.